[RETRACTED] Challenges and Breakthroughs in the Production of Composite Materials from Sustainable and Renewable Resources - Md Moin Kadir; Jubaer Akon Pranto; Md Mehedi Hasan Mia (Control Systems and Optimization Letters, 2026)
Following a rigorous, careful concerns and considered review of the article published in the Control Systems and Optimization Letters, to article entitled "Challenges and Breakthroughs in the Production of Composite Materials from Sustainable and Renewable Resources," Vol. 4, No. 1, pp. 1-7, 2026, https://doi.org/10.59247/csol.v4i1.122.This paper has been found to be in violation of the Control System and Optimization Letters Publication principles and has been retracted.The article contained redundant material; the editor investigated and found that the paper was published in Scientia. Technology, Science and Society, Vol. 2, No. 8, pp. 61-72, 2025, DOI: https://doi.org/10.59324/stss.2025.2(8).06, entitled "Challenges and Breakthroughs in the Production of Composite Materials from Sustainable and Renewable Resources".The document and its content have been removed from the Control Systems and Optimization Letters, and reasonable effort should be made to remove all references to this article.